2010
DOI: 10.1093/alcalc/agp087
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Factors Determining Survival of Alcoholic Withdrawal Syndrome Patients in a General Hospital

Abstract: The factors determining survival after admission to a general hospital for alcoholic withdrawal syndrome depend on the intensity of clinical manifestations (delirium tremens, ICU, orotracheal intubation) and the presence of associated comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 27 publications
5
63
3
1
Order By: Relevance
“…In symptomatic therapy, benzodiazepines are the drugs of choice; in some regions, clomethiazole is used as well [72][73][74][75][76][77][78] . In alcohol withdrawal delirium, supportive therapy is essential as well.…”
Section: Symptomatic and Supportive Treatmentmentioning
confidence: 99%
“…In symptomatic therapy, benzodiazepines are the drugs of choice; in some regions, clomethiazole is used as well [72][73][74][75][76][77][78] . In alcohol withdrawal delirium, supportive therapy is essential as well.…”
Section: Symptomatic and Supportive Treatmentmentioning
confidence: 99%
“…Evidence 50 indicates that patients who have a medical or surgical illness in whom AWS develops have a higher predisposition for more severe withdrawal and delirium tremens than do patients who have AWS only. Most likely the situation is the same for patients with a critical illness and AWS.…”
Section: Severe Aws and Delirium Tremensmentioning
confidence: 99%
“…However, in general, little research has been done on the influence of critical illness on delirium tremens and vice versa. 50 Most recently, Sohraby et al 48 reported the results of a retrospective cohort study of critically ill patients with severe AWS. The findings indicated that this population of patients may need additional drugs to manage severe withdrawal.…”
Section: Severe Aws and Delirium Tremensmentioning
confidence: 99%
“…Además, se asocia a incrementos del riesgo de infección nosocomial, de requerir ventilación mecánica y de la mortalidad 24,25 . De ahí la necesidad de identificar aquellos enfermos con un mayor riesgo de presentar formas graves de síndrome de abstinencia, especialmente en el ambiente hospitalario.…”
Section: Manifestaciones Clínicasunclassified